Serrodyne Frequency Translation Using Time-Modulated Metasurfaces - Wu, Zhanni; Grbic, Anthony (IEEE transactions on antennas and propagation, 2020)
Temporally modulated metamaterials have attracted significant attention recently due to their nonreciprocal and frequency converting properties. Here, a transparent, time-modulated metasurface, which functions as a serrodyne frequency translator, is reported at X -band frequencies. With a simple biasing architecture, the metasurface provides electrically tunable transmission phase that covers 360°. A sawtooth waveform is used to modulate the metasurface, allowing Doppler-like frequency translation. Modal analysis of an analogous time-modulated medium is performed to gain insight into the operation of the metasurface-based serrodyne frequency translator. Two such metasurfaces can be cascaded together to achieve magnetless devices that perform either phase or amplitude nonreciprocity.